PUBLIKASI PEMBERITAAN DALAM PEMBENTUKAN CITRA LEMBAGA - Mukaromah Mukaromah; Amida Yusriana (Islamic Communication Journal, 2019)
Mass media is one of the media publications to the public in the formation of the Image. Important positive images are formed to foster public trust. News in the newspaper media is still interesting to be appointed in an effort to build a positive image of educational institutions. In addition to targeting the masses of young people, higher education institutions also target parents who are still familiar with conventional media such as newspapers. The case study in this study was Dian Nuswantoro University (Udinus) and news in the Suara Merdeka newspaper. Suara Merdeka is interesting to be appointed because the local  central Java newspaper has amounts of printing and is still an alternative reading in the Central Java region where this segmentation is in line with Udinus segmentation which is domiciled in Semarang, Central Java.This study aims to analyze the theme of news that often arises about the institution, the frequency of occurrence of coverage in certain periodizations. Furthermore, this can be observed how the reporting of a media that has the power to shape the image of the institution. The method used is quantitative content analysis, which describes how the contents of the media using thematic and physical recording units are analyzed using the concept of public relations about media and the formation of the image of the institution. The result can be seen that there are 9 sections in Suara Merdeka which present Udinus related news, namely Semarang Metro rubric, Edukasia, Screen, Page 1, Business Economy, Around Young Tugu, Salatiga News, Youth Voice Expressions. Screen Rubric occupies the highest position in the news, which is 70.3%. For thetheme that is often reported, there are four types of reporting, namely news related to the world of academics (products), related to environmental responsibility (CSR), reporting related the environment and reporting relatedto the activities of communicating the activities of the institution.